The Effect of Type 2 Diabetes Mellitus on Osteopenia and Vertebral Fractures in Elderly Women - Zeynep Koç (Galenos Yayinevi, 2022)
Objective:In our study, we examined the effects of type 2 diabetes mellitus (DM) on the thoracic and lumbar vertebrae in patients with osteopenia.Materials and Methods:Ninety patients had type 2 DM while 64 patients did not have any chronic disease. We analyzed the patients' total lumbar T-score with dual energy X-ray absorptiometry. We included patients with a T-score between -1 and -2.4 and evaluated the thoracic and lumbar vertebrae of the patients with dorsal and ventral X-ray imaging.Results:In the results of the study in which we examined 154 osteopenic female patients, we found the mean osteopenia depth to be -1.52 in individuals with type 2 DM and -1.74 in the control group. We found the lumbar T value to be statistically significantly higher than the control group cases (p=0.001; p<0.01). However, the fracture rate was 21.9% in the control group, while it was 36.7% in type 2 DM. We found the fracture rate in patients with type 2 DM to be statistically significantly higher than that in the control group (p=0.049; p<0.05). In the control group, 64.3% of the fractures were grade 1, and 35.7% were grade 2, and there was no collapse fracture, while in the group with diabetes, we found grade 1 fractures 24.2%, grade 2 27.3%, and grade 3 collapse fractures 48.5%. Notably the incidence and severity of fractures was significantly higher than the control group, however, the lumbar T-score in the presence of type 2 DM was not as low as the control group in our study.Conclusion:Although the lumbar T-score in the presence of the type 2 DM was not as low as the control group in our study, it is noteworthy that the incidence and severity of fractures was significantly higher than the control group.